Income Inequality and Political Trust: Do Fairness Perceptions Matter? - Licia Bobzien (Social Indicators Research, 2023)
Political trust—in terms of trust in political institutions—is an important precondition for the functioning and stability of democracy. One widely studied determinant of political trust is income inequality. While the empirical finding that societies with lower levels of income inequality have higher levels of trust is well established, the exact ways in which income inequality affects political trust remain unclear. Past research has shown that individuals oftentimes have biased perceptions of inequality. Considering potentially biased inequality~perceptions, I argue that individuals compare their perceptions of inequality to their preference for inequality. If they identify a gap between what they perceive and what they prefer (= fairness gap ), they consider their attitudes towards inequality unrepresented. This, in turn, reduces trust in political institutions. Using three waves of the ESS and the ISSP in a cross-country perspective, I find~that (1) perceiving a larger fairness gap is associated with lower levels of political trust; (2) the fairness gap mediates the link between actual inequality and political trust; and (3) disaggregating the fairness gap measure, political trust is more strongly linked to variation in inequality perceptions than to variation in inequality preferences. This indicates that inequality perceptions are an important factor shaping trust into political institutions.
Keywords: 300; Political trust; Inequality; Perceptions of inequality; Fairness